Developmental plasticity of coordinated action patterns in the perinatal rat. Issue 4 (4th March 2015) - Brumley, Michele R.; Kauer, Sierra D.; Swann, Hillary E.; Brumley, Michele R.
ABSTRACT Some of the most simple, stereotyped, reflexive, and spinal‐mediated motor behaviors expressed by animals display a level of flexibility and plasticity that is not always recognized. We discuss several examples of how coordinated action patterns have been shown to be flexible and adaptive in response to sensory feedback. We focus on interlimb and intralimb coordination during the expression of two action patterns (stepping and the leg extension response) in newborn rats, as well as interlimb motor learning. We also discuss the idea that the spinal cord is a major site for supporting plasticity in the developing motor system. An implication of this research is that normally occurring sensory stimulation during the perinatal period influences the typical development and expression of action patterns, and that exploiting the developmental plasticity of the motor system may lead to improved strategies for promoting recovery of function in human infants with motor disorders. © 2015 Wiley Periodicals, Inc. Dev Psychobiol 57: 409–420, 2015.